2017
DOI: 10.1155/2017/1656053
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Lipid Droplets in Cancer and Cancer Stem Cells

Abstract: For decades, lipid droplets have been considered as the main cellular organelles involved in the fat storage, because of their lipid composition. However, in recent years, some new and totally unexpected roles have been discovered for them: (i) they are active sites for synthesis and storage of inflammatory mediators, and (ii) they are key players in cancer cells and tissues, especially in cancer stem cells. In this review, we summarize the main concepts related to the lipid droplet structure and function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 203 publications
(257 reference statements)
7
165
0
3
Order By: Relevance
“…Our results support the new discovered functions of the lipid droplets that include activity in the synthesis and storage of inflammatory mediators in cancer cells [37,54]. The proteins associated with lipid droplets cover the surface of the membrane monolayer and participate in the lipid droplets formation, growth, transport, and catabolism [54]. It has been found that some protein components that are present on the lipid droplet surfaces are derived from endoplasmic reticulum (ER) and the enzymes involved in TAG and CE synthesis reside on the ER membrane [55,56].…”
Section: It Is Evident Fromsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results support the new discovered functions of the lipid droplets that include activity in the synthesis and storage of inflammatory mediators in cancer cells [37,54]. The proteins associated with lipid droplets cover the surface of the membrane monolayer and participate in the lipid droplets formation, growth, transport, and catabolism [54]. It has been found that some protein components that are present on the lipid droplet surfaces are derived from endoplasmic reticulum (ER) and the enzymes involved in TAG and CE synthesis reside on the ER membrane [55,56].…”
Section: It Is Evident Fromsupporting
confidence: 85%
“…Our results support the new discovered functions of the lipid droplets that include activity in the synthesis and storage of inflammatory mediators in cancer cells [37,54]. The proteins associated with lipid droplets cover the surface of the membrane monolayer and participate in the lipid droplets formation, growth, transport, and catabolism [54].…”
Section: It Is Evident Fromsupporting
confidence: 83%
“…Lipid droplets are organelles present in living cells and are composed of neutral lipids, primarily triglycerides and sterol esters. Recent literature reveals a clear relationship between alteration of LD expression and cancer cell stemness, high tumor grade and aggressiveness . To show the potential of our SRS microscope towards quantitative imaging of lipids, and in particular its ability to characterize their saturation level through a high‐resolution spectral scan of the whole fingerprint‐to‐CH‐stretch bandwidth, we have measured three vegetable edible oils with different lipid saturation levels as test samples.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous studies that showed that the polarity of lipid droplets of cancer cells is lower than that of normal cells due to the specic lipid metabolism of cancer cells. 21,32 The cytoplasmic polarity value was between those of the lysosomes and lipid droplets, and the F yellow /F red uorescence ratio values in the cytoplasm of Chang, Huh7, SW837, and HeLa were 1.0, 0.87, 0.91, and 0.81, similar to that of 2-PrOH. In particular, the F yellow /F red uorescence ratios provided information about the polarity of solvents similar to that of lysosomes (1.7-1.9, MeOH and water), cytoplasm (0.81-1.0, 2-PrOH), and lipid droplets (0.15-0.43, DMF and EA).…”
Section: Resultsmentioning
confidence: 84%